Startup company development - Labeika, Aliaksei; Novotný, Ota, 1971-; Daněk, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
At the present time, the ideas of establishing own business is becoming relatively popular. Thanks to Internet growth, modern types of companies, startups, are gaining greater attention, particularly among young people. Unfortunately, too many startups fail within first years. One of the most ordinary reasons of that lies in the lack of the structural approach for hypotheses' testing. To overcome high risk of the setback, it is recommended to study methodologies of startups' creation, which provide guidelines and clear step-by-step processes' description. Thus, the thesis depicts startups' context and provides a comparison of several approaches of startups' development based on Lean Startup Methodology with studies of S. Blank, E. Ries and especially, D. Novoselcev. Moreover, it describes the process of a real-life business idea development, concerning internships' organizing, based on D. Novoselcev's approach, business modeling and elements of experience management. Finally, due to findings obtained during application of the methodology on the real case and literature review, the initial D. Novoselcev's methodology was amended and described in the last part of the thesis.
Vedoucí práce: Ota Novotný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses